Changes in Fathers' Body Mass Index, Sleep, and Diet From Prebirth to 12 Months Postbirth: Exploring the Moderating Roles of Parenthood Experience and Coparenting Support. Issue 12 (1st March 2021) - Lo, Brian K; Kang, Augustine W; Haneuse, Sebastien; Yu, Xinting; Ash, Tayla von; Redline, Susan; Taveras, Elsie M; Davison, Kirsten K
Abstract: Background: While research has examined prenatal to postnatal changes in women's weight, sleep, and diet, much less is known about these changes among fathers. Purpose: This study aimed to (a) examine changes in fathers' body mass index (BMI), sleep, and diet from 1 month before birth to 5–6 months following birth, and from 5–6 months to 11–12 months following birth and (b) explore the moderating roles of parenthood experience and coparenting support. Methods: 169 fathers (mean age 35.5 years, 58.9% White) participated. Fathers completed an intake survey shortly after their infant's birth to recall their height and weight, nighttime sleep hours, fruit and vegetable intake, soda intake, and fast food intake for the month prior to birth. When their child was 6 and 12 months old, fathers reported their weight, sleep, and diet again for the past 4 weeks (i.e., 4 week periods spanning 5–6 months and 11–12 months following birth). Generalized estimating equations were used to answer our research questions. Results: Fathers reported higher BMI (Δ = 0.22 kg/m 2 ; 95% confidence interval [CI] = 0.06, 0.38; p = .008) and less nighttime sleep duration (Δ = −0.21 hr; 95% CI = −0.38, −0.05; p = .012) at 5–6 months following birth compared to 1 month prior to birth. Fathers' diet remained stable over the three timepoints. No evidence was found to support the moderating roles of parenthood experience and coparenting support on fathers' weight and behavior changes. Conclusions: 5–6 months following birth may be an important point of intervention for fathers to promote a return to prebirth BMI and sleep levels. Abstract : Among fathers in the Rise & SHINE study, regardless of their parenthood experience and coparenting support, fathers in general gained weight and lost sleep in the first 5-6 months following birth.